2016
DOI: 10.1007/s10903-016-0385-3
|View full text |Cite
|
Sign up to set email alerts
|

Men from Sub-Saharan Africa Living in Worker Hostels in France: A Hidden Population with Poor Access to HIV Testing

Abstract: Delayed presentation to care among HIV-infected individuals continued to be frequent in France. Migrants are at high risk for late presentation. This cross-sectional study investigated barriers to HIV testing in the specific population of men from sub-Saharan Africa living in four migrant worker hostels in Paris, France. Factors associated with never having been tested for HIV were examined using logistic regression. In all, 550 men participated, coming mainly from Mali and Senegal, with 31 % having lived in F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Our findings are consistent with research findings from other sub-Saharan African countries, including Zambia, South Africa and Burkina Faso where overall HIV testing rates for men is disproportionately lower than among women [10,11,73]. This suggests that men in the SSA region may face similar barriers to HIV testing at different levels including at the individual, health-care system, and interpersonal levels where perceived negative provider attitudes, location and set up of health facilities, inconvenient operating hours, and low perception of risk create barriers to HIV testing and increase the risk of HIV infection [9,12,17,25,50].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are consistent with research findings from other sub-Saharan African countries, including Zambia, South Africa and Burkina Faso where overall HIV testing rates for men is disproportionately lower than among women [10,11,73]. This suggests that men in the SSA region may face similar barriers to HIV testing at different levels including at the individual, health-care system, and interpersonal levels where perceived negative provider attitudes, location and set up of health facilities, inconvenient operating hours, and low perception of risk create barriers to HIV testing and increase the risk of HIV infection [9,12,17,25,50].…”
Section: Discussionmentioning
confidence: 99%
“…HIV testing services (HTS) is a major feature of Kenya's HIV response [4] as it offers timely linkage to care and treatment, prevention of onward transmission to sexual partners and reduction of risky behaviors [5][6][7][8]. However, major challenges in the HIV care cascade remain for men [9][10][11][12][13][14][15][16][17][18]. Recent population-based evidence from Kenya demonstrated that, 53% of women had tested for HIV in the past 12 months and received their results, compared to 45% of men [19].…”
Section: Introductionmentioning
confidence: 99%